A bibliometric and visualization analysis on the association between chronic exposure to fine particulate matter and cancer risk - Luo, Xuman; Yang, Qiuping; Zheng, Daitian; Tian, Huiting; Chen, Lingzhi; Wu, Jinyao; Ji, Zeqi; Chen, Yexi; Li, Zhiyang (Frontiers in Public Health, 2022)
As one of the major pollutants in ambient air pollution, fine particulate matter (PM2.5) has grasped public attention and plenty of laboratory and epidemiological research has implied adverse consequences of PM2.5 exposure on human health. To investigate its association with the commonly observed PM-related cancer, a bibliometric study was performed on related publications from 2012 to 2021 from a macroscopic perspective with the help of the Web of Science database and scientometric software VOSviewer, CiteSpace V, HistCite, and Biblioshiny. The results indicated that of 1948 enrolled documents, the scientific productions were steadily increasing and hit the peak in 2020 with publications of 348. The most prolific author, journal, organization, and country were Raaschou-Nielsen O, Science of the Total Environment, Chinese Academy of Sciences, and China respectively. The top five keywords in frequency were "air pollution", "particulate matter", "lung cancer", "exposure" and "mortality". The toxic mechanism of carcinogenicity was explained and is worthy of further investigation. China and the US co-worked most closely and it is hoped countries can strengthen cooperation to take control of air pollution together. There also exists a need to identify the components of PM2.5 and refine the models to assess the global burden of disease attributed to PM2.5 exposure.